An update on the prevalence of metabolic syndrome and its associated factors in rural northeast China - Yu, Shasha (BioMed Central, 2014)
BACKGROUND: The last study reported the prevalence of Metabolic Syndrome (MetS) in rural Northeast China was conducted approximately ten years ago. We aimed to update the data on the prevalence and epidemiological features of MetS in rural Northeast China. METHODS: This survey was conducted from July 2012 to August 2013. In this study, a total of 11,496 residents from the rural Northeast China were randomly selected and examined. MetS was defined according to the ATPIII-modified criteria. Data regarding the demographic and lifestyle characteristics and the blood biochemical indexes of these participants were collected by well-trained personnel. RESULTS: The prevalence of MetS was 39.0% and was more prevalent in women than in men (45.6% vs. 31.4%, P < 0.001). Elevated blood pressure was the most common metabolic disorder in both genders (71.7% in males and 63.3% in females). Only 11.2% and 9.6% of males and females, respectively, in this study had no metabolic disorders. Multivariate logistic regression, after adjusting for possible confounders, revealed the following factors that increased the risk of MetS: being female, older age, having more than one child, a family income of >20,000 CNY per year, longer sleep duration (>9 h/d), chronic disease status, frequent consumption of beans or bean products and frequent tea drinking. Completion of education through middle school, moderate physical activity and smoking were correlated with lower rates of MetS. CONCLUSION: The prevalence of MetS was high in the rural areas of China, especially among females. In addition to some of the more conventional risk factors associated with MetS, including age, sex, annual income and educational status, we also found that having more than one child and frequent consumption of tea and beans were risk factors for MetS, while smoking was a common factor among those that did not have MetS in rural Northeast China.